2017
DOI: 10.1080/14728222.2017.1311325
|View full text |Cite
|
Sign up to set email alerts
|

KSR as a therapeutic target for Ras-dependent cancers

Abstract: Introduction Targeting downstream effectors required for oncogenic Ras signaling is a potential alternative or complement to the development of more direct approaches targeting Ras in the treatment of Ras-dependent cancers. Areas covered Here we review literature pertaining to the molecular scaffold Kinase Suppressor of Ras (KSR) and its role in promoting signals critical to tumor maintenance. We summarize the phenotypes in knockout models, describe the role of KSR in cancer, and outline the structure and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 80 publications
0
40
0
Order By: Relevance
“…We have therefore used an unbiased affinity proteomics approach to catalog cytoplasmic interactors of the human NRAS 5′-UTR rG4. This rG4 was selected due to the relevance of NRAS in tumorigenesis ( 22 ). Moreover, folding of the NRAS rG4 into a stable parallel intramolecular G4 is well-characterized biophysically and this rG4 has been shown to inhibit translation in vitro ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have therefore used an unbiased affinity proteomics approach to catalog cytoplasmic interactors of the human NRAS 5′-UTR rG4. This rG4 was selected due to the relevance of NRAS in tumorigenesis ( 22 ). Moreover, folding of the NRAS rG4 into a stable parallel intramolecular G4 is well-characterized biophysically and this rG4 has been shown to inhibit translation in vitro ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Steven PD et al [19] reported that suppression of KSR1 gene expression could prolong survival in patients with colorectal cancer, and McCall JL et al [20] reported that the KSR1 gene affects Myc protein expression which affects the prognosis of patients with colon cancer. In addition, Neilsen BL [21] reported that KSR1 could be a therapeutic target for Ras-dependent cancers. With all the studies done on KSR1 , this is the first time KSR1 has been reported to affect the prognosis of patients with TETs.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have demonstrated that the gene mutation of Ras is closely associated with the occurrence of malignancy 11,12. An interesting study demonstrated that Ras-ERK1/2 activation played a crucial role during tumor maintenance and which might be particularly important for the treatment of Ras-driven cancers 13. However, how the mutation of Ras affects the development of OS is still needed for further research.…”
Section: Introductionmentioning
confidence: 99%